In silico prediction of silver nitrate nanoparticles and Nitrate Reductase A (NAR A) interaction in the treatment of infectious disease causing clinical strains of E. coli - Mohamed Ragab AbdelGawwad; Ensar Mahmutović; Dunia A. Al Farraj; Mohamed Soliman Elshikh (Elsevier, 2020)
Background: The interaction of specially designed nanoparticles with proteins is the basis of formation of a nanoparticle-protein corona. Silver nanoparticles and molecules have been used in many fields due to their strong antimicrobial activity against pathogenic microorganisms such as bacteria, yeast and fungi. E. coli is a Gram-negative bacteria that has the genome completely sequenced and determined majority of its protein 3D structures. Nitrate Reductase A is a cellular protein often found in many bacteria that uses nitrate as an electron acceptor during anaerobic growth. The enzyme is composed of three different chains α, β and γ, all having properties of metal binding regions and domains. Methods: Bioinformatics tools were used to investigate the structure, domains, interactomes, and docking sites of E. coli Nitrate Reductase A in order to predict the possible site of interaction of silver nitrate AgNO3 with the protein. The 3D structure of the NAR A protein was predicted with the Phyre2 protein modeling software. The generated structures from Phyre2 were validated and evaluated by analysis of Ramachandran plots using RAMPAGE online software. To understand the evolutionary relationships between the subunits of Nitrate Reductase A, a phylogenetic tree was constructed using Phylogeny.fr. Results: All cysteine and histidine residues in amino acid sequences were identified; 3D structure of subunits predicted together with Ramachandran plots, and the electrostatic potential was computed using various bioinformatics tools. The reactive cationic property of silver ion leads to attachment to specific anionic regions and active sites of the three subunits causing in many prokaryotic cells deactivation of nitrate reductase. Obtained results showed the possible sites of attachment of silver ions and their reactivity with domains that have metal bonding properties. In silico analysis of silver nanoparticles and nitrate reductase is helpful to treat various infections diseases caused by E. coli.